2015
DOI: 10.1007/s00266-015-0575-8
|View full text |Cite
|
Sign up to set email alerts
|

Flap Failure and Wound Complications in Autologous Breast Reconstruction: A National Perspective

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 24 publications
5
42
1
Order By: Relevance
“…Finally, 85% of respondents would not recommend riskreducing mastectomy for patients with BRCA deleterious mutations. These data agree with the recommendations to avoid or delay major surgery that could prolong hospitalization and increase complications or require further hospital admissions [46][47][48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 85%
“…Finally, 85% of respondents would not recommend riskreducing mastectomy for patients with BRCA deleterious mutations. These data agree with the recommendations to avoid or delay major surgery that could prolong hospitalization and increase complications or require further hospital admissions [46][47][48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 85%
“…715 There was 1 patient (3%) who had fat necrosis but no flap loss in our study, but Kim et al 22 reported 14.2% of fat necrosis in their large Asian patient study, and Massenburg et al 23 reported that the prevalence of flap failure was 2.7% in TRAM flaps and 2.4% in free flaps for autologous breast reconstruction. 20 This might be because we had a small number of the patients in our study and all patients were nonsmokers.…”
Section: Discussionmentioning
confidence: 52%
“…Limitations can significantly impact activities of daily living and leisure time pursuits for the first 3 months, but function generally begins to return to baseline between 6 and 12 months postoperatively. 33 Abdominal flaps donor sites are accompanied by some degree of donor-site morbidity, which can include asymmetry, bulge, or hernia. The incidence of abdominal hernia following pedicled TRAM flap reconstruction is cited between 1.2% and 8.8%.…”
Section: Hazards and Costs Associated With Crrmmentioning
confidence: 99%